Feelings of Loneliness due to COVID‑19 Pandemic’s Home Confinement/ Quarantine and its Relationship with Anxiety Traits and Empathy - Pereira, Joana (2022)
Introduction: We aimed to understand how loneliness and empathy relate to home confinement/quarantine and to explore the relation between loneliness, anxiety traits and empathy. Methods: This is an observational cross‑sectional cohort study including 364 participants. We delivered an online questionnaire composed by UCLA Loneliness scale (assessing loneliness), STAI‑Y (assessing trait anxiety), and IRI (assessing empathy). For the statistical analysis we performed  descriptive and inferential statistics. When not‑otherwise specified, two‑tailed p<0.05 was considered significant. Results: The mean for IRI was 60.46 (SD: 10.88), for UCLA Loneliness scale was 32.70 (SD: 8.11) and for STAI‑Y was 42.01 (SD: 12.29). We found no statistically significant correlation between empathy and loneliness (p>0.05). Nonetheless, loneliness and anxiety traits were positively correlated (p<0.05), and psychiatric comorbidity was associated with higher levels of loneliness and anxiety traits (p<0.05). Conclusion: Our results suggest social cohesion, solidarity and continuous online contact may have played a significant role on preservation of empathy and feelings of loneliness. The fact that loneliness may be felt in a positive way (such tightening household relationships) can explain the non‑correlationbetween the last and empathy. Ultimately, the positive correlation between anxiety traits and loneliness underlines the vulnerability of previously anxious subjects, enhancing the importance of promoting mental health during the pandemic.